Disappearance Rate of 133Xe from the Dog Liver with Different Routes of Administration - Aronsen, K. F.; Ericsson, B.; Lindell, S. E.; Nylander, G. (Nuklearmedizin - NuclearMedicine, 1968)
In anaesthetized dogs the disappearance rate of 133Xe injected into the liver parenchyma was much slower than that of 133Xe injected into the hepatic artery, while the highest disappearance rate was obtained when the isotope was injected into the portal vein. Vasopressin reduced the disappearance rate of 133Xe injected into the portal vein considerably without changing the disappearance rates for the isotope injected into the hepatic artery or directly into the liver parenchyma.